Hockey : stats, facts, and figures - Mikoley, Kate (Mikoley, Kate. Do math with sports stats!, 2018)
Introduces the sport of hockey by examining some of the key statistics and math elements involved, such as the size of the neutral zone, the number of minutes played, and the percentage of face-off wins. Includes color photographs, text-dependent math questions, a glossary of terms, and an index.